Malignant Mixed Epithelial and Stromal Tumor of the Kidney: Report of a Carcinosarcoma Case and an Updated Literature Review. (April 2023) - Yu, Jiaqi; Yu, Shili; Jia, Meng; Gao, Hongwen; Sun, Ping-Li
Mixed epithelial and stromal tumors of the kidney (MESTK) are rare and recently defined entities that comprise both epithelial and stromal cells. MESTK is mostly benign; however, to date, 18 borderline or malignant cases have been reported. In this study, we report a case of carcinosarcoma exhibiting a large carcinoma and small sarcoma component, and review the relevant literature. The patient was a 59-year-old woman who presented with a large mass in the left kidney having solid and focal cystic components. The patient underwent left radical nephrectomy. The tumor was gray-white and solid-cystic, with a relatively clear boundary. Microscopically, the tumor revealed benign and malignant components. The benign component consisted of multiple tubules, variable-sized cysts lined with benign epithelium, and hyalinized stroma. The malignant component was composed of predominantly small cell neuroendocrine carcinoma and a small quantity of adenocarcinoma, squamous cell carcinoma, and sarcoma. Finally, a diagnosis of the malignant MESTK was made. Certain cases of borderline or malignant transformation of MESTK have been published, so it is important to enhance findings made by other studies.